Auditor Characteristics and Audit Report Lag: Industry Specialization and Long Tenure as Moderating Variables - Wiedjaja, Debby Audrey; Eriandani, Rizky (Jurnal Dinamika Akuntansi, 2021)
Purpose: This study aims to analyze the effect of audit tenure and auditor workload on Audit Report Lag (ARL) and provide empirical evidence of whether the selection of industry-specialized auditors and audit partners with specific workloads can weaken this relationship.Method: This research was conducted using moderated regression analysis. Selection of the research sample using purposive sampling method, from all public listed companies during 2015-2017, 945 firm years were selected.Finding: This study found that audit tenure moderately significantly negatively affects ARL. Besides, this study can also prove that partners with heavy workloads can lead to longer ARL. However, a long partner-client relationship can weaken the workload and ARL relationship because of the auditor's more familiarity and information. Based on these results, the characteristics of auditors affect the timeliness of audit reporting.Novelty: This study enriched the literature by finding out how to deal with audit delay effectively, whereas previous research only focused on identifying ARL causes. This research's implication is expected to provide broader insight to the company regarding several factors that can help companies issue their financial reports on time when the auditors have high workloads and short tenures.